[Ladner, Kate (soprano) : programs and related material collected by the National Library of Australia]
Material in the Australian performing arts programs and ephemera (PROMPT) collection consists of programs and related items for Australian performing arts organisations, Australian artists performing overseas, professional productions performed in Australia (including those featuring overseas performers) and overseas performances of Australian plays, music, etc.
Kate Ladner was born in Adelaide, South Australia and studied singing at the Queensland Conservatorium of Music. In 1992-93, Kate was a principal young artist with two major Australian opera companies and in 1994, she won the Australian Opera Trust prize. She moved to London in 1995 to begin her European career; performing throughout England, Ireland, Germany and Austria. She continues to be a regular guest artist in Australia.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Ladner, Kate -- Miscellanea; Opera singers -- Australia -- Miscellanea; Sopranos (singers) -- Australia -- Miscellanea; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian